Placental Chorangiosis: An Important Pattern of Placental Injury - Banu Doğan Gün; Figen Barut; Alper Tanrıverdi; Şükrü Oğuz Özdamar; Aykut Barut (Medical Network, 2006)
OBJECTIVE: Chorangiosis is an infrequently diagnosed placental lesion characterized by placental capillary proliferation. In this study we present 10 cases of chorangiosis with histological and immunhistochemical features and described the clinical effects on fetal outcome. STUDY DESIGN: Ten cases of chorangiosis (7%) diagnosed in 150 placentas examined at our institution between 2002 and 2004 were evaluated. Chorangiosis was defined as the presence of aminimum of 10 villi, each with 10 or more vascular channels, in 10 or more areas of three or more random areas when using an x10 objective. Beside histopathological criteria, histochemical and immunohistochemical staining was also applied. RESULTS: Chorangiosis was most commonly associated with cesarean section (60%), preterm birth and neonatal intensive care (40%), Apgar scores of 5 minute or less (30%), maternal disease and drug ingestion (30%). Also intervillous hemorrhage (80%), placental calcification (60%), placentomegaly (40%), umbilical cord knots (40%), chorioamnionitis (40%), perivillous fibrin (40%) and umbilical vein dilatation (40%) were commonly observed placental findings in chorangiosis cases. CONCLUSION: Chorangiosis should be considered as an important sign of placental injury associated with hy poxia in utero. Histopathological recognition of these lesions might help to determine the underlying and proximate causes of fetal injury.